Konsistensi Tuntutan Jaksa Dalam Tindak Pidana Penipuan Dilihat Dari Asas Dominis Litis. - Anatasya Awalia S. Hasan; Fence M. Wantu; Julisa Aprilia Kaluku (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
Criminal disparity refers to dissenting judgments regarding the same criminal act or one that possesses dangerous characteristics, both of which can be compared without clear justification. This research aims to understand and analyze whether the existence of disparities in prosecution can fulfill the legal perspectives’s objectives and to identify and analyze the factors causing disparities in prosecution in Cases Number: 176/Pid.B/2019/PN Gto and Cases Number: 163/Pid.B/2019/PN Gto by using a normative research method with a case approach. The technique employed involves a literature review supported by descriptive analysis a supplementary method. The research findings are as follows: firstly, in both verdicts, Number 176/Pid.B/2019.PN Gto and Number 163/Pid.B/2019/PN Gto, it is observed that they still do not fully meet the legal perspective’s objectives because there are legal objectives that remain unfulfilled. Secondly, both verdicts contain factors influencing the occurrence of disparities in prosecution, including the consequences caused, considerations from the prepator’s prespective, personal factors, aggravating and mitigating circumstances, and the extent of the losses incurred.